Online Marketing of Food Products through Marketplace Platform: A Study of Community Based Online Marketplace of BEDUKMUTU - Akhmadi Heri; Pratolo Suryo (E3S Web of Conferences, 2021)
Online food marketing through a marketplace platform has been a trend in today’s food product marketing, especially with the COVID-19 pandemic that has increased food product purchases through online platforms. Bedukmutu is an online marketplace platform developed by Universitas Muhammadiyah Yogyakarta (UMY) that provides food product transactions and other products and services. This paper investigated the Bedukmutu marketplace business model in the marketing of food products and how far the Muhammadiyah community ties influence the consumers. Descriptive analysis, website observation, and in-depth interviews with Bedukmutu stakeholders were utilized to explore the extent of online food product marketing practices in this marketplace. The results revealed several key factors in the Bedukmutu business model on food products marketing, including entrepreneurship as a value proposition with the consumer to consumer e-commerce (C2C) model and Muhammadiyah network as a key partner in market development. The offered food products vary from fresh to processed food originating from traders within students, employees and Muhammadiyah community networks. The implementation of purchasing incentives in measuring the performance of UMY employees is one of the motivations for consumer demand (demand-pull) apart from the affiliation factor with Muhammadiyah organizations (community-based).